PENGARUH PENERAPAN TEORI BRUNER TERHADAP HASIL BELAJAR MATEMATIKA KELAS III SEKOLAH DASAR - Marlina, Lia; Margiati, K.Y; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the influence of the application of Bruner's learning theory to students' learning outcomes in third grade of State Elementary School 35 South Pontianak. The research method used experimental with quasi experimental design (form quasi experimental design) with form of Nonequivalent Control Group Design. The sample in this study is a population sample with class III B as control class and class III A as experiment class chosen by simple random sampling. The data was collected in the form of an essay test. The results of this study were t tested t (count) of 2.4941 and t(table) (Î± = 5% and dk = 20 + 24 - 2 = 42) , 6827. Because t count (2.4941> t table (1.6827), thus Ha is accepted and Ho is rejected. The result of calculation of effect size of the result data of the control class students and the experimental class is 0.68 is classified in medium category, it can be concluded that the application of Bruner's learning theory gives a moderate impact on student learning outcomes in learning mathematics in class III State Elementary School 35 South Pontianak.Â Keywords: Bruner Theory, Learning Outcomes, Mathematics